2006
DOI: 10.1002/pds.1306
|View full text |Cite
|
Sign up to set email alerts
|

Trends in potentially inappropriate prescribing amongst older UK primary care patients

Abstract: Prescription of potentially inappropriate medication, particularly benzodiazepines, to older people remains at a high level in the UK. Levels were higher than those seen in published data from the Netherlands, however the low rate of co-proxamol prescribing in the Netherlands explains much, but not all, of the difference. Future international comparisons, based on more careful delineation of the criteria, may play a valuable role in pharmaco-vigilance and can identify areas where regulation of prescribing may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 14 publications
3
47
1
3
Order By: Relevance
“…A high proportion of the potential IP identified in a Portuguese primary care study, using the Beers' ID tool only, was attributable to ticlopidine (14.9%) [13], a medicine not licensed for use in Ireland. A large number of general practices (n = 131) were involved in the study conducted in the UK, which reported a potential IP rate of 24.8% [14]. However, the rate of potential IP is less in other European centres (9.8% in Turkey and 12.5% in Finland) [9,11] compared with centres in the USA (21.3%, 23.5%, 28.8%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high proportion of the potential IP identified in a Portuguese primary care study, using the Beers' ID tool only, was attributable to ticlopidine (14.9%) [13], a medicine not licensed for use in Ireland. A large number of general practices (n = 131) were involved in the study conducted in the UK, which reported a potential IP rate of 24.8% [14]. However, the rate of potential IP is less in other European centres (9.8% in Turkey and 12.5% in Finland) [9,11] compared with centres in the USA (21.3%, 23.5%, 28.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate prescription of long-acting benzodiazepines in older patients has been highlighted repeatedly in the literature over the last 25 years, in particular given the link with falls and fracture risk and the difficulties with successful withdrawal [35][36][37]. Despite this, long-acting benzodiazepines continue to be initiated and repeatedly prescribed for older patients in primary and secondary care in Ireland and other countries [10,[12][13][14]. These realities suggest that long-acting benzodiazepines should not be initiated in older patients, given their high propensity for psychological and physical dependency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In other studies that used the 2003 version of the Beers criteria, the PIMs that were most prescribed were long-action benzodiazepines, propoxyphene, amitriptyline and antihistamines. 10,12,14,27,33 Estrogen, muscle relaxants, ticlopidine, chlordiazepoxide and anti-inflammatory agents have also been cited. 12,27,33 In Brazil, Carvalho observed that anti-inflammatory agents, methyldopa, digoxin and benzodiazepines with long half-life were the PIMs most used by elderly people in the city of São Paulo.…”
Section: 212326mentioning
confidence: 99%
“…10,12,14,27,33 Estrogen, muscle relaxants, ticlopidine, chlordiazepoxide and anti-inflammatory agents have also been cited. 12,27,33 In Brazil, Carvalho observed that anti-inflammatory agents, methyldopa, digoxin and benzodiazepines with long half-life were the PIMs most used by elderly people in the city of São Paulo. 16 Gorzoni observed that benzodiazepines, methyldopa, ergot derivatives and cyclandelate were the drugs most often found in analyses on medical files.…”
Section: 212326mentioning
confidence: 99%